2006
DOI: 10.1209/epl/i2006-10194-5
|View full text |Cite
|
Sign up to set email alerts
|

The glass transition and liquid-gas spinodal boundaries of metastable liquids

Abstract: A liquid can exist under conditions of thermodynamic stability or metastability within boundaries defined by the liquid-gas spinodal and the glass transition line. The relationship between these boundaries has been investigated previously using computer simulations, the energy landscape formalism, and simplified model calculations. We calculate these stability boundaries semi-analytically for a model glass forming liquid, employing accurate liquid state theory and a first-principles approach to the glass trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We further note that such an arrested phase separation scheme also applies to the case of longer-range attractive potential. Studies of a Lennard-Jones potential [162,163] and of a larger (15%) SW model [164], for which the Noro-Frenkel mapping does not apply, have also reported that the glass line meets the two-phase region on the right-hand side of the critical point.…”
Section: (Non-equilibrium) Gelation As Arrested Phase Separationmentioning
confidence: 99%
“…We further note that such an arrested phase separation scheme also applies to the case of longer-range attractive potential. Studies of a Lennard-Jones potential [162,163] and of a larger (15%) SW model [164], for which the Noro-Frenkel mapping does not apply, have also reported that the glass line meets the two-phase region on the right-hand side of the critical point.…”
Section: (Non-equilibrium) Gelation As Arrested Phase Separationmentioning
confidence: 99%
“…14 Later work suggests that the liquid spinodal and glass transition line do intersect at ρ S , however, they do so at finite temperature. 30,33,40 FIG. 2.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the establishment of conditions such that a connected percolating structure able to sustain stress survives for times longer than the observation time is often preempted by phase separation. For spherical attractive interaction potentials, it has been found that phase separation is always dominant at low densities and arrested states at low packing fractions φ can be reached only in non-homogeneous state, whose morphology is determined by the phase separation process [13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%